Genomic and functional portrait of multidrug-resistant, hydrogen sulfide (H2S)-producing variants of Escherichia coli - Mazumder, Razib; Hussain, Arif; Rahman, Mohammad Mustafizur; Phelan, Jody E.; Campino, Susana; Abdullah, Ahmed; Clark, Taane G.; Mondal, Dinesh (Frontiers in Microbiology, 2023)
Atypical Escherichia coli forms exhibit unusual characteristics compared to typical strains.The H2S-producing variants of some atypical E. coli strains cause a wide range of illnesses in humans and animals. However, there are sparse reports on such strains worldwide. We performed whole-genome sequencing (WGS) and detailed characterisation of four H2Sproducing E. coli variants from poultry and human clinical sources in Dhaka, Bangladesh. All four isolates were confirmed as E. coli using biochemical tests and genomic analysis, and were multidrug-resistant (MDR). WGS analysis including an additional Chinese strain, revealed diverse STs among the five H2S-producing E. coli genomes, with Clonal complex ST10 being detected in 2 out of 5 genomes. The predominant phylogroup detected was group A (n=4/5).The blaTEM1B (n=5/5) was the most predominant extended-spectrum beta-lactamase (ESBL) gene, followed by different alleles of blaCTX-M (blaCTX-M -55,-65,-123; n=3/5). Multiple plasmid replicons were detected, with IncX being the most common. One E. coli strain was classified as enteropathogenic E. coli. The genomes of all five isolates harboured five primary and four secondary function genes related to H2S production. These findings suggest the potential of these isolates to cause disease and spread antibiotic resistance. Therefore, such atypical E. coli forms should be included in differential diagnosis to understand the pathogenicity, antimicrobial resistance and evolution of H2S-producing E. coli.